Ablution Intervention with Prompting Techniques to Improve Gross Motor Imitation Skills of ADHD Children - Arifin, Tazul; Tarsidi, Iding; Ratnawati, Andayani (Angstrom Centre of Education, 2023)
One of the characteristics of children with Attention Deficit Hyperactivity Disorder (ADHD) is difficulty paying attention and difficulty listening. This can hinder children with ADHD in learning to imitate, such as imitating activities that use gross motor skills. This study aims to determine the effectiveness of interventions using ablution movements with prompting techniques in improving the imitation gross motor skills of children with ADHD. The method used is an experimental method with the type of single subject research (SSR) and using the ABA design on one child with ADHD. The results of the study find that ablution interventions with appropriate prompting techniques according to children's abilities could improve the gross motor imitation skills of children with ADHD, this is evidenced by the increase in the average gross motor imitation ability of the subjects from 15.9% to 86.3% after being intervened 30 sessions. The improvement in gross motor imitation skills involving the hands is getting better, but the subject had not been able to distinguish which one is right and left when not given a verbal command.